PERCEIVED STRESS AND ACADEMIC PERFORMANCE IN MEDICAL STUDENTS - Mancevska, Sanja; Pislevski, Matej; Pluncevic Gligoroska, Jasmina (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
The aim of the study was to assess the levels of stress and perceived academic performance in medical students from all study years enrolled at Faculty of Medicine, UKIM, Skopje during the winter semester of the academic year 2022/23. An online survey including the Perceived Stress Questionnaire (PSQ), Perceived Academic Performance Scale (PAPS) and a questionnaire regarding demographic variables (age and gender) was available via Google Forms to a cohort of students at three time points (the beginning, the middle and the end) of the semester. A total of 113 students from all years, aged 18-28, responded. Eighty percent of them were female and 20% were male.  The PSQ is self-report questionnaire comprised of 30 questions, which asses the stressful life events during past month. The score can range from 0 to 1, with a higher score indicating a higher level of stress. The PAPS consists of five statements on the experience of one's academic performance, achievement and success. The score can range from 5 to 35, with a higher score indicating a more positively perceived academic performance. The mean value of PSQ score increased (0.55±0.2; 0.58±0.22; 0.63±0.16) (p=0.0286), followed by a decrease in the mean value of PAPS (27.1±6.4; 25.7±7.1; 25.3±7.5) (p=0.1369) from the first to the third time point. A gradual increase in perceived stress and reduced academic performance among medical students during the winter semester are observed. Key words: PSQ, PAPS, medical students.